Two compounds of the Colombian algae Hypnea musciformis prevent oxidative damage in human low density lipoproteins LDLs - Gladys Rozo; Claudia Rozo; Mónica Puyana; Freddy A. Ramos; Carmen Almonacid; Henry Castro (Journal of Functional Foods, 2019)
People of the Caribbean believe that red algae have properties that are beneficial to human health. We aimed to test the beneficial properties of Hypnea musciformis by measuring its ability to prevent oxidation in human LDLs. We obtained algal extracts via supercritical fluid extraction using 15 different combinations of pressure, temperature and solvent polarity. We quantified phenol contents and measured antioxidant activity through ABTS and TBARS assays. The ability of each extracted compound to protect LDLs against oxidative damage was compared with that of natural vitamin E. The extracts obtained under low pressure (10–20 MPa) with 8% ethanol provided 42% extra protection, while those obtained under high pressure (30 MPa) with 8% ethanol provided 62.5% extra protection. The compounds responsible for this activity were purified through chromatography and identified by 1HNMR spectroscopy as (−)-epicatechin and phloretin. Our results emphasize the high potential of extracts of H. musciformis as functional foods.